Campanian ammonites and nannofossils from southern Limburg, the Netherlands - Jagt, J; Burnett, J; Kennedy, W (1995)
New records of ammonites and nannofossil assemblages from the Vaals Formation northeast of Cottessen and at Raren close to the Netherlands/Belgium border include Pachydiscus (Pachydiscus) subrobustus Seunes, 1892, Hoplitoplacenticeras (Hoplitoplacenticeras) marroti (Coquand, 1859) and Scaphites (Scaphites) hippocrepis (DeKay, 1828) III sensu Cobban, 1969, while the Zeven Wegen Member (Gulpen Formation) at Zeven Wegen (Vijlenerbosch) yields Scaphites (Scaphites) gibbus Schluter, 1872, the Cottessen and Zeven Wegen ammonite horizons being referred to nannofossil zone CC/B 20 of the Boreal scheme. -Authors